SLOW TOURISM SEBAGAI KONSEP, PRAKTIK DAN PELUANG KEBIJAKAN KEPARIWISATAAN BERKELANJUTAN DI KABUPATEN LINGGA - Fitraturrahmi; Zainul Ikhwan (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
Abstrack : The Lingga Cluster in the Riau Islands Province holds significant potential for nature- and culture-based tourism, yet its development has not fully embraced sustainability principles. This study aims to formulate slow tourism as a strategic approach for sustainable tourism development in the region. A descriptive qualitative method was employed through literature review, field observation, and in-depth interviews with key stakeholders. The findings reveal that slow tourism enhances the quality of travel experiences by promoting relaxed travel, direct interaction with local communities, and appreciation of cultural and environmental values. Proposed strategies include active community involvement in destination management, development of experience-based tourism products, promotion rooted in local wisdom, and provision of eco-friendly infrastructure. This concept aligns with the geographical and social characteristics of the Lingga Cluster, which consists of a network of small islands with unique natural and cultural features. The implementation of slow tourism is expected to not only foster local economic growth but also strengthen environmental conservation and cultural heritage preservation. These recommendations serve as a policy direction for balanced tourism development that integrates economic, social, and ecological dimensions in island regions. Keywords: slow tourism; sustainable tourism; Lingga Cluster; local wisdom; community participation